2018
DOI: 10.1093/icvts/ivy072
|View full text |Cite
|
Sign up to set email alerts
|

The differences in histological changes among pulmonary vessels divided with an energy device

Abstract: Surgeons should consider that dividing the pulmonary vessels with a vessel-sealing device might have more histological impact on the layers of the wall of the PA than on those of the PV, although it remains unclear whether these findings constitute a clinical risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Adenocarcinoma is the most common form of lung cancer and has recently been classified into pre-invasive adenocarcinoma [atypical adenocarcinoma hyperplasia (AAH), adenocarcinoma in situ (AIS)], minimally invasive adenocarcinoma (MIA), and invasive adenocarcinoma (IAC) (3). The 5-year disease-free survival rates in AIS and MIA are 100% or close to 100%, which are significantly higher than that in IAC (38-86%, depending on the predominant histological subtypes) (4,5). Therefore, the accurate preoperative diagnosis of lung adenocarcinoma is critical for clinical decision-making processes and the assessment of prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…Adenocarcinoma is the most common form of lung cancer and has recently been classified into pre-invasive adenocarcinoma [atypical adenocarcinoma hyperplasia (AAH), adenocarcinoma in situ (AIS)], minimally invasive adenocarcinoma (MIA), and invasive adenocarcinoma (IAC) (3). The 5-year disease-free survival rates in AIS and MIA are 100% or close to 100%, which are significantly higher than that in IAC (38-86%, depending on the predominant histological subtypes) (4,5). Therefore, the accurate preoperative diagnosis of lung adenocarcinoma is critical for clinical decision-making processes and the assessment of prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…In histological and immunohistochemical analysis of pulmonary vessels divided by LigaSure, it was found that LigaSure sealing result in sealing of the adventitia only, without complete fusion of the layers of the PA walls. It remains unclear whether these findings have a clinical impact (6,7). As a first step for using energy devices in anatomical lung resections, the proximal side of the pulmonary branch were ligated and just after sealed and divided with the devices (10,11).…”
Section: Energy Sealing Devices In Anatomical Lung Resectionmentioning
confidence: 99%